Meningkatkan Sikap Gotong Royong dan Hasil Belajar Pakat Melalui Model PBL Fase E - Afra Ramani; Ansel Joko Prayitno (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
This study was conducted at SMAN 2 Sengah Temila, where many students exhibited low literacy and numeracy skills, resulting in decreased learning motivation. To address this issue, the researcher implemented the Problem-Based Learning (PBL) model. The objectives of the study were to determine: (1) the extent to which the PBL model improves students’ mutual cooperation attitudes; (2) the extent to which it enhances learning outcomes; and (3) the extent to which it increases learning mastery. This classroom action research (CAR) was carried out in two cycles, each consisting of four stages: planning, implementation, observation, and reflection. The research subjects were 25 students. Data collection techniques included tests, observations, and documentation, with data analyzed descriptively and presented in graphs and tables. In the first cycle, cognitive test results showed that 20% of students were categorized as very good, 36% good, 16% sufficient, and 28% developing. The target was 50% very good, 45% good, 5% sufficient, and 0% developing. In the second cycle, there was a significant improvement, with 72% of students achieving the very good category and 28% in the good category, surpassing the target of 70% and 30%, respectively. The sufficient and developing categories reached 0%, as targeted. The findings demonstrate that the PBL model effectively improves student learning outcomes and fosters cooperative attitudes, validating its use as a successful approach to achieving learning objectives in classrooms with low academic motivation.